2017
DOI: 10.1016/j.kint.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 receptor antagonist, oxidized adenosine triphosphate, ameliorates renal ischemia-reperfusion injury by expansion of regulatory T cells

Abstract: Extracellular adenosine triphosphate (ATP) binds to purinergic receptors and, as a danger molecule, promotes inflammatory responses. Here we tested whether periodate-oxidized ATP (oATP), a P2X7 receptor (P2X7R) antagonist can attenuate renal ischemia-reperfusion injury and clarify the related cellular mechanisms. Treatment with oATP prior to ischemia-reperfusion injury decreased blood urea nitrogen, serum creatinine, the tubular injury score, and tubular epithelial cell apoptosis after injury. The infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…IRI is caused by blood flow perfusion after long-term organ ischemia, which can delay recovery of organ functions or even bring damages to tissues and organs (10). Reperfusion may also cause tissue damage, cell apoptosis and necrosis, which has great damage to the tissues and organs of patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…IRI is caused by blood flow perfusion after long-term organ ischemia, which can delay recovery of organ functions or even bring damages to tissues and organs (10). Reperfusion may also cause tissue damage, cell apoptosis and necrosis, which has great damage to the tissues and organs of patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…77 Other interventions potentially mediated by modulating Tregs include a protective role for microRNA 26a (Mir-26a), which plays functional roles in cell differentiation, growth, apoptosis and metastasis, and modulates Th17/Treg balance, 78 and a P2X7 receptor antagonist, periodate-oxidised ATP (oATP). 79 As in other experimental models, in IRI IL-2/anti-IL-2 mAb complexes administered prior to IRI increased Tregs (in the spleen and kidney), resulting in less renal dysfunction and tubular injury, and when given after IRI, they promoted functional recovery and inhibited renal fibrosis. 80 As IL-2 and IL-33 promote the expansion of murine Tregs in vivo, Stremska et al generated an IL-2 and IL-33 fusion cytokine that they termed IL-233, and which they found increased the recruitment of Tregs into the kidney and protected mice from IRI more efficiently than either cytokine alone.…”
Section: Ischaemia-reperfusion Injurymentioning
confidence: 77%
“…Transfer of human‐umbilical cord blood‐derived MSCs has similar effects . Other interventions potentially mediated by modulating Tregs include a protective role for microRNA 26a (Mir‐26a), which plays functional roles in cell differentiation, growth, apoptosis and metastasis, and modulates Th17/Treg balance, and a P2X7 receptor antagonist, periodate‐oxidised ATP (oATP) . As in other experimental models, in IRI IL‐2/anti‐IL‐2 mAb complexes administered prior to IRI increased Tregs (in the spleen and kidney), resulting in less renal dysfunction and tubular injury, and when given after IRI, they promoted functional recovery and inhibited renal fibrosis .…”
Section: Acute Kidney Injurymentioning
confidence: 98%
“…On the other hand, deficiency of CD73 activity was shown to be beneficial in mild kidney IRI, suggesting a novel protective role for AMP‐mediated signaling . Koo et al demonstrated that a P2X7 receptor antagonist (or P2X7 receptor deficiency in hematopoietic cells) ameliorates murine renal IRI by expansion of regulatory T (Treg) cells. Similarly, apyrase treatment to degrade extracellular ATP protected mice from both acute and chronic renal IRI …”
Section: Targeting Atp In Iri and Graft Preservationmentioning
confidence: 99%
“…On the other hand, deficiency of CD73 activity was shown to be beneficial in mild kidney IRI, suggesting a novel protective role for AMP-mediated signaling. 31 Koo et al 32 Outcomes from liver transplant have also been tied to adenine nucleotide levels and manipulation of ATP-mediated signaling.…”
Section: A3rmentioning
confidence: 99%